Diabetes care : a practical manual - Hillson, Rowan ([Oxford] : Oxford University Press, 2015)
Written in a friendly, easy-to-read way, with summaries for quick reference and detailed information when needed, this book is aimed at health care professionals in primary, community and secondary care, helping experienced staff update their knowledge, and acting as a quick guide for those new to diabetes.
This edition previously issued in print: 2015.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 24, 2016).
Keywords: Diabetics -- Care; Diabetes -- Treatment